LISTRIK SEBAGAI KO-PRODUK POTENSIAL PABRIK GULA - Yahya Kurniawan; H. Santoso (Badan Penelitian dan Pengembangan Pertanian, 2009)
Electricity as a potential co-product of sugar factoryGlobal energy crisis not only impact the increase in electricity price but also influence the shortage of electricity supply, so that the development of bioenergy as a potential renewable energy resource needs to be accomplished. Sugar cane is the potential energy resource to produce electricity. Some sugar producing countries have already sold electricity surplus to local company. Electricity production was about 150 kWh/ton of cane by using technology of condensing/extraction turbines (TCE). Moreover, new technology by using biomass integrated gasification to gas turbines (BIG-GT) was able to produce 300 kWh/ton of cane. Production of electricity by using TCE technology is potential to be applied in some sugar factories in Indonesia. The potential of electricity production in the near future is estimated around 379,310 MWH from surplus of bagasse and around 1,029,630 MWH from trash, so that the total potency of electricity production from sugar cane is about 1,408,940 MWH.